DGI-002 Adrenal Insufficiency Induced by a Chinese Herbal Medicine. (12th March 2013) - Kieran, M; Gavin, C; O'Shea, L; Brady, J; Meegan, C
Abstract : Background: Chinese herbal medicines have a history, dating back to 1974, of containing strong prescription drugs [1]. In the United States (US), Food and Drug Authority (FDA) analysis of Chinese herbal preparations has found prednisolone, diazepam, paracetamol, indomethacin and hydrochlorothiazide [1]. During a routine review for type 2 diabetes, a MMUH patient reported new-onset fatigue. In view of the presenting complaint, a Synacthen test and thyroid function tests were performed. The patient's Synacthen test reported positive for adrenal insufficiency, despite an absence of other clinical symptoms. Repeat testing and external analysis confirmed the result. Potential causes of the positive Synacthen test were investigated. On further questioning the patient admitted to taking a 'vitamin-type' tablet, which was a Chinese herbal medicine, Cow's Head Brand, Tung Shueh Pills. It was a suspected that the Tung Shueh Pills may have contained corticosteroids, which suppressed the patient's endogenous corticosteroid production, producing a positive Synacthen test. Purpose: To find out whether Cow's Head Brand, Tung Shueh Pills contained corticosteroids. Materials and Methods: Literature review for reports on Cow's Head Brand, Tung Shueh Pills. Analysis of Cow's Head Brand, Tung Shueh Pills in collaboration with the Irish Medicines Board (IMB) Results: Cow's Head Brand, Tung Shueh Pills manufactured by the Ta Ang Pharmaceutical Company are included on a FDA list of products that require detention when being imported into the US [1]. There is also a case report of Tung Shueh Pills causing acute interstitial nephritis [2]. Review of the listed ingredients of the Tung Shueh pills did not identify any agents known to suppress endogenous corticosteroid production. The IMB analysis of the agent reported that the product contained betamethasone, arsenic, lead, cadmium and antimony The patient is currently receiving oral hydrocortisone, which is being tapered in accordance with Synacthen test results. Conclusions: Cow's Head Brand, Tung Shueh pills were found to contain a corticosteroid and heavy metals. Regular administration resulted in suppression of endogenous corticosteroid production, producing drug-induced adrenal insufficiency in a patient. This case report highlights the importance of including herbal medicines in patients' medicines histories. It also highlights that a lack of regulation of Chinese Herbal Medicines enables inclusion of prescription agents, not included in the product ingredients, which may have significant pharmacological effects on patients. References: FDA Import Alert #66-10, issued 18th March 2011. http://www .accessdata.fda.gov/cms_ia/importalert_173.html Diamond, JR, Pallone, TL. (1994). Acute interstitial nephritis following use of Tung Shueh Pills. Am J Kidney Disease 24(2), 219–221. No conflict of interest.